Fluvial-aeolian interaction deposits in intermontane valleys: modern and ancient examples (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Arid to semiarid regions usually show a close interaction between fluvial and aeolian processes resulting in a particular pattern of landforms and sedimentary facies (Langford, 1989; Langford and Chan, 1989). Here we present a characterization of the fluvial-aeolian interaction environment and its distinctive facies, both in modern settings (Guandacol Valley, La Rioja province) and in a sedimentary section of the Vinchina Formation (Northwestern Pampean Ranges). Recognition of these interaction facies in ancient sequences becomes critical not only because of its paleoenvironmental and paleoclimatic significance but also on account of its potential importance as reservoir rocks (Ellis, 1993; Meadows and Beach, 1993). Methodology in Guandacol Valley included mapping of subenvironments by remote sensing and field survey, definition, characterization and sampling of landforms, textural analysis of sediments and description of stratification styles in natural exposures. In the ancient fluvial-aeolian deposits main lithofacies and facies association were identified and described, together with the characterization of sandstones by petrographic studies.Fluvial-aeolian interaction environment in Guandacol Valley (Figs. 1 and 2) is characterized by an ephemeral high-energy gravelly-sandy braidplain associated with abundant aeolian landforms (Tripaldi y Limarino, 1998; Tripaldi, 2002, Tripaldi et al., 2003). This region presents an arid/semiarid regime with average annual precipitations of 130 mm, focus on spring and summer. Two subenvironments have been distinguished in the Guandacol Valley, channel and floodplains (Table 3). The former comprises different kinds of fluvial bars, channel bed deposits and aeolian landforms (Fig. 3). Since most of the year channels remain dry and vegetation cover is scarce, wind action reworked fluvial sediments, determining aeolian rippled mantles and sand shadows (Figs. 4 and 5). According to grain size and morphology two kinds of ripples were recognized in Guandacol Valley: sand aeolian ripples and granule aeolian ripples (Sharp, 1963; Fig. 4). Floodplains are dominated by aeolian landforms (rippled aeolian mantles, sand shadows, zibars, protodunes and dunes; Figs. 6 and 7), with subordinated fluvial deposits (gravelly-sandy overflow mantles and cracked mud drapes; Figs. 6 and 7). Floodplains show an irregular and rolling sandy topography shaped by the emerging of protodunes that evolve to dunes, as well as by the vertical growth of sand shadows and zibars. Although the aeolian sediments could be partially eroded during flood, their importance results from their capacity of producing different types of interactions with fluvial currents. Aeolian bedforms not only can cause temporary dam streams and disruption of the fluvial drainage network (Langford, 1989), but also can supply high quantities of sands promoting rapid saturation of the flooding currents and the consequent amelioration of the flow erosive power.Ancient fluvial-aeolian interaction deposits of the Vinchina Formation (Turner, 1964) are characterized by thin aeolian sandstone bodies interfingered with fluvial rip-up clast conglomerates, sandstones and mudstones deposited in ephemeral meandering plains (Fig. 8). Aeolian levels are 10 to 40-cm thick, tabular to lentiform bodies of well sorted fine to very fine sandstones, showing a very thin parallel or low angle cross-lamination (Fig. 9). Dune deposits were scarcely identified in the studied fluvial-aeolian succession. Remarkable features in the aeolian beds include: 1) inversely graded laminae (product of wind ripple migration), 2) unimodal, symmetrical or positive asymmetric, well to very well sorted sand, 3) open packing and high porosity in sandstones, 4) very low matrix percentage, 5) lack of muddy intraclasts, upper regime structures (as parting lineation) and erosive surfaces, 6) high index ripple forms with coarsest grains at the crest, 7) occurrence of some beds of medium to very coarse (occasionally granule), bimodal sandstones, with parallel to low angle cross-lamination and inversely graded laminae, owing to the development of granule ripples by wind reworking of fluvial sands (Table 4).
Keywords: Aeolian; Fluvial; Present environments; Paleoenvironments; Intermontane valleys.